A New Historical Reading of the Subversion of the Patriarchal ‘Juridico-Discursive’ Power in Victorian Period: Elizabeth Robins, Suffrage Drama, and the Concept of ’New Women’ - Najar, Esmaeil; Kazemifar, Reza (k@ta: A Biannual Publication on the Study of Language and Literature, 2016)
In this research, we employ a socio-historical examination of the subversion of the ‘juridico-discursive’ power in the late Victorian period in order to examine the rise of the British Suffrage Movement and specifically ‘suffrage drama’. we demonstrate how ordinary women and women artists, here in case of Elizabeth Robins, moved against the patriarchal artistic hegemony. The term ‘artistic hegemony’ is utilized here as a parallel term for ‘cultural hegemony’. In Marxism, and specifically in Gramscian theories, cultural hegemony refers to the domination of socio-cultural norms imposed by ruling class (bourgeoisie) on a society. These ideological norms are usually practiced through sets of diverse apparatuses commensurate with different social-class statutes. How this process (consciously or unconsciously, deliberately or accidently) occurred in the English Victorian society is not of concern in this study; however, we depict how marginalized groups, women in general, challenged the dominant overpowering apparatuses, whose power Michel Foucault believed to be ‘juridico-discursive’. We study how women, from the margins of the British society, challenged British ruling patriarchal foundations in the late nineteenth and early twentieth century and put an end to its negative up-to-down ‘juridico-discursive’ power. As one of the controlling apparatuses of the ruling class is always art and literature, we discuss how dramatic literature and theatre, specially through the concept of ‘suffrage drama’, as a ‘place of tolerance’ in a Foucauldian term, function as antitheses to the mainstream theatre in the setting of suffrage movement.